Description of Clinical Severity, Laboratory Results, and ECG of COVID-19 Patients Who Received Doses I and II of the COVID-19 Vaccine at Haji Adam Malik General Hospital from April to August 2021 - Shafira Pramesi Putri; Andika Sitepu; Yuke Sarastri; Setia Putra Tarigan (Journal of Endocrinology, Tropical Medicine, and Infectious Disease (JETROMI), 2022)
Introduction: COVID-19 patients with comorbidities (hypertension or cardiovascular disease) have a high mortality rate and are at high risk of showing severe symptoms of COVID-19. One of the preventions to avoid COVID-19 is to vaccinate against COVID-19. The COVID-19 vaccine has proven safe and effective in patients with comorbidities because the vaccine can prevent severe symptoms of COVID-19. Aim: To describe the clinical severity, laboratory results, and ECG of COVID-19 patients with cardiovascular comorbidities who received the first and second doses of COVID-19 vaccination at Haji Adam Malik General Hospital from April to August 2021. Methods: A descriptive retrospective study using a cross-sectional study design. Total sampling was used, which fits the inclusion and exclusion criteria. Results: Out of the 71 COVID-19 patients with cardiovascular comorbidities, the majority were found to be male patients (57.7%), aged â‰¥ 65 years (22.5%), with comorbid hypertension (84.5%), and had received vaccine dose II (97.2%). Most patients had mild symptoms (47.9%), abnormal ECG results (73.2%), and varied laboratory results. Conclusion: Most patients had received the second COVID-19 vaccine, showing moderate symptoms of COVID-19, abnormal ECG results, and varied laboratory results.